Pemetaan Komputasi Bibliometrik Analisis Pembelajaran Google Classroom Menggunakan Vosviewer - Opi Irmayani; Salwa Nur Albania; Asep Nuryadin (Universitas Indraprasta PGRI Jakarta, 2023)
This research discusses the development of Google Classroom in education using bibliometric methods with VOSviewer. The data was retrieved from Google Scholar through the Publish or Perish reference manager, and 277 relevant articles were found. The analysis reveals fluctuations in Google Classroom and Learning research over the past 10 years (2013-2022). Only one study was conducted in 2013, none in 2014-2015. There were 2 studies in 2016, 3 in 2017, 10 in 2018, 19 in 2019, and 50 in 2020. In 2021, the number doubled to 112 journals, and 80 studies were conducted until October 2022. The popularity of research related to Google Classroom and Learning tends to increase, especially in 2021, experiencing a twofold growth. Research topics include models, e-learning, blended learning, teaching, English, Covid-19, online learning, research, Google Classroom media, issues, effects, influences, motivation, teachers, and pandemics. However, blended learning remains relatively underexplored, providing a foundation for further research in this field.